The rise of positivism and the seeds of social constructivism in the social sciences Durkheim and Weber - De Ungria, Maria Corazon A. University Researcher III, College of Science, Natural Science and Research InstitutePhilosophy; Arlante, Salvacion M. University Librarian, UP Diliman; Tan, Merle C. Director, UP NISMED; Cordero, Rosa R. University Research III, UP National College of Public Administration and Governance; Disierto, Diane A. Law Reform Specialist, UP College of Law.; Office of Vice-President for Academic Affairs; UP Diliman Interactive Learning Center; UP Open University Media Center; UP Computer Center (Quezon City University of the Philippines Diliman, 2006)
The contribution of sociologist acknowledge founding scholars Durkheim and Weber to the nature of social reality and the claims to knowing such reality, their penetrating insights shift this hope and methods of social research not only on thier time but up to the present contentions between the agent of structure as well as the additional material factors and social behavior. The lecture also gives an overview of the major ideas of these two social thinkers.
Summary from the moderator.
DVD
Executive director: Celia Adriano; Director: Grace Javier Alfonso; Assistant director: Arminda Santiago; Associate producer: Karmen Rivera-Angobung; Floor director: Judith Garcia; Online floor director; Myra Jill Siason
Moderator: Malaya Ronas.
Keywords: Constructivism; Positivism